THE EXISTENCE OF MINORITIES IN THE SPECIFICITY OF ISLAMIC SYIAR IN ACEH, INDONESIA - Hasan Basri M. Nur; Syed Sultan Bee Packeer Mohamed; Nor Azlah Sham Rambely (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2020)
The Majority (98,91%) of Aceh population are Muslims. Other religious followers are hardly in number (minority) in Aceh; Christian (0,79%), Catholic (0,19%), Buddhist (0,11%), and Hinduism (0,00%).  The Muslim majority of Aceh population pushed the Indonesian government to granted special right in order to implement Islamic syi’ar and Islamic law in Aceh. Life of minority of other religious followers, often become an attention from Aceh outsiders. Aceh geographic location on international maritime belt allowed its community to get in touched with different civilizations, stimulated openness and tolerance for its peoples. Islamic mission model without violence in Aceh in early days established humanism that make minority fell safe among syi’ar and sharia (Islamic law) implementation in Aceh. Nevertheless, there is little obstacle among believers’ relationship in Aceh Singkil District. To keep believers live in harmony, minorities who are comers to respect local wisdom which are characterized fully with Islamic nuance and protected by Indonesia law. Keywords: Minority, Islamic Syi’ar, Aceh